Flexural strength comparison of self-synthesised porcelain with the sintering temperature of 1150 degree Celsius and 1200 degree Celsius - Gunawan, Joseph; Taufik, Dede; Takarini, Veni; Hasratiningsih, Zulia (Universitas Padjadjaran, 2018)
Introduction: Porcelain must have sufficient flexural strength to withstand mastication forces. The flexural strength of porcelain can be influenced by the maturity level of porcelain related to the temperature and sintering time. The purpose of this study was to compare the flexural strength of Indonesian natural sand self-synthesised porcelain with different sintering temperatures. Methods: Self-synthesised porcelain powder, with the composition of 65% Pangaribuan felspar, 25% Belitung silica, 5% Sukabumi kaolin, and 5% potassium salt, were condensed into 10 samples with the size of 7cm x 2cm x 0.4cm. A total of 5 samples were each burned at the temperature of 1150°C and 1200°C. Flexural strength test was performed using the Universal Testing Machine (Netzsch™) with the lowest load of 7.5 kg, and the data obtained was calculated using the bending strength formula. Result: The average flexural strength of self-synthesised porcelain at the sintering temperature of 1150°C was 26.678 MPa, while at the temperature of 1200°C was 39.038 MPa. Conclusion: This study concluded that Indonesian natural sand self-synthesised porcelain had a lower flexural strength at the sintering temperature of 1150°C than at the temperature of 1200°C.Keywords: Flexural strength, self-synthesised porcelain, sintering temperature.